Triangulation of theories on the excellence of the McKinsey 7S business model (Journal of Universal Excellence, 2026)
Research question / Hypothesis (RQ): The study was based on identifying key differences between individual authors, who used the McKinsey 7S model in their researches. Purpose: The purpose of this study was to identify and highlight the conflicting conclusions, which we got on the basis of studying articles by various authors, whose studies were carried out with the McKinsey 7S model. Method: The methodology of our study was based on a triangulation of various authors, whose studies were carried out with the already mentioned business model. We also identified the methodology of studies from individual authors.Results: In our research, we got the expected different authors’ interpretations, concerning the applicability of the McKinsey 7S business model. Some authors note that the model lacks on important variables or that some of them need to be replaced, but then again, other say that the model is sufficient and not to be changed. Organization: The analysis shows that the effectiveness of the organization largely depends on the traditionally less involved employees, consumers and partners in the direct decision-making, which can only be influenced by »soft indicators«.Company: The inclusion of the model’s soft factors presents the key impact on the company, which relates to the social responsibility to all company’s stakeholders, as well as the inclusion of cornerstones, which would update the model in terms of electronic use, in order to show the responsibility towards the environment. Originality: We prepared the latest overview of the findings, based on the studied literature and resources in the field of the McKinsey 7S business model. The research of theories was substantiated with our own research on the influential factors of the model; we presented the McKinsey 7S model in an appropriate comprehensive manner, in a way that has not been dealt with up till now and which is an unsearched field in the world scientific literature. Limitations / further research: Limitations in this research present the differences between individual articles, due to the different purposes, methodologies and research questions of their research. Suggestions for further research are related in particular to the update of the relatively outdated model (1980).
Keywords: business model; model of excellence; McKinsey 7S; management’s molecule; triangulation of theories